2001
DOI: 10.1002/1529-0131(200104)45:2<191::aid-anr173>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in three ethnic groups. VIII. Predictors of early mortality in the LUMINA cohort

Abstract: Objective To determine the features associated with mortality in a multiethnic US cohort of patients with systemic lupus erythematosus (SLE) within 5 years of study onset. Methods Socioeconomic and demographic features (age, gender, ethnicity, marital status, education, occupation, poverty, and health‐related behaviors [drinking, smoking, exercising]), clinical and immunologic features (disease duration, disease onset type, disease activity according to the Systemic Lupus Activity Measure [SLAM], disease damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
98
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(109 citation statements)
references
References 82 publications
(109 reference statements)
8
98
1
2
Order By: Relevance
“…52 The concept of damage in SLE has become an important outcome measure, as it not only predicts mortality also functional capacity and health resource utilization. [53][54][55] In this review, three measures of injury have been identified, one that is completed by the doctor, the SDI, and 2 to be completed by the patient LDIQ and BILD. The 2 self-administered measures of damage showed a good correlation with the extent to which the physician measured was considered the gold standard.…”
Section: Discussionsupporting
confidence: 69%
“…52 The concept of damage in SLE has become an important outcome measure, as it not only predicts mortality also functional capacity and health resource utilization. [53][54][55] In this review, three measures of injury have been identified, one that is completed by the doctor, the SDI, and 2 to be completed by the patient LDIQ and BILD. The 2 self-administered measures of damage showed a good correlation with the extent to which the physician measured was considered the gold standard.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, in the multivariate analysis, interestingly, the occupation variable presented a tendency to associate with a higher frequency of excess weight (p = 0.055). Few studies have evaluated this variable when describing socio-demographic characteristics, [25].…”
Section: Discussionmentioning
confidence: 99%
“…Important differences were detected in clinical and immunogenetic variables that could help identify associations with clinical manifestations, disease activity, and physician's global scores. The epidemiology of SLE has been evaluated mainly in North America [2][3][4][5][6][7][8][9][10][11]21,27,29,48,[54][55][56]64,76,77,81,84 and in some European countries 17,19,20,[38][39][40]42,46 , but little information is available from Latin America 1,16,22,23,26,36,37,41,47,49,51,52,65,79 . For obvious reasons, the Latin American studies make few comparisons between ethnic groups, although some have shown a poor prognosis and a high prevalence of infections in African-Latin American (ALA) SLE patients, both of which may relate to socioeconomic variables.…”
Section: Introductionmentioning
confidence: 96%
“…The LUMINA study has compared clinical, socioeconomic status, and disease-related variables in 3 ethnic groups in clinical centers in the United States [4][5][6][7][8]10,11,15,27,64,84 . Important differences were detected in clinical and immunogenetic variables that could help identify associations with clinical manifestations, disease activity, and physician's global scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation